Artes visuais e tecnologias na educação: história e contemporaneidade - Vazquez, Cecilia; Medeiros, Rosângela Fachel de; Pozzi, Marion Divério Faria; Souza, Adrise Ferreira de (Revista GEARTE, 2019)
Apresentação